Enhancement the Flux of VDF-co-HFP Hollow Fiber Membranes for Direct Contact Membrane Distillation Applications - Rashid, Khalid T.; Sunarti, Abd Rahman (Asian Research Publishing Network (ARPN), 2016)
Phase inversion technique has been utilized to prepare Poly (vinylidene fluoride-co-hexafluoropropylene) PVDF- co-HFP, hollow fiber membranes. Polyvinylpyrrolidone (PVP) with 9 wt. %. added as a pore former additives to the polymer dope solution. Characteristics of the PVDF-co-HFP hollow fiber membrane with / without PVP particles have been studied. It was found that the membrane prepared without PVP additives has a low porosity and a high contact angle. Existence the PVP additives of 9 wt. % causing the increase of the membrane porosity by 28 %.Whilst increase PVP content resulting in decrease of membrane hydrophobicity. MD experiment was done using a direct contact membrane distillation (DCMD) configuration as crucial test to investigate performance of product PVDF-co-HFP hollow fiber membrane. Increase the amount of PVP to 9 wt. % in dope solution, this in turn leads to an increased the permeate flux from of 4.5 to 15.8 Kg/m2.h at 70 oC The effect of operating conditions such as feed temperature, concentration of feed solution and permeate flow pattern on the performance flux of the hollow fiber membranes were studied.